Leader Narcissism and Outcomes in Organizations: A Review at Multiple Levels of Analysis and Implications for Future Research - Braun, Susanne (Frontiers in Psychology, 2017)
Narcissists often pursue leadership and are selected for leadership positions by others. At the same time, they act in their own best interest, putting the needs and interests of others at risk. While theoretical arguments clearly link narcissism and leadership, the question whether leader narcissism is good or bad for organizations and their members remains unanswered. Narcissism seems to have two sides, a bright and a dark one. This systematic literature review seeks to contribute to the ongoing academic discussion about the positive or negative impact of leader narcissism in organizations. 45 original research articles were categorized according to outcomes at three levels of analysis: the dyadic level (focusing on leader-follower relationships), the team level (focusing on work teams and small groups), and the organizational level. On this basis, we first summarized the current state of knowledge about the impact that leader narcissism has on outcomes at different levels of analysis. Next, we revealed similarities and contradictions between research findings within and across levels of analysis, highlighting persistent inconsistencies concerning the question whether leader narcissism has positive or negative consequences. Finally, we outlined theoretical and methodological implications for future studies of leader narcissism. This multi-level perspective ascertains a new, systematic view of leader narcissism and its consequences for organizations and their stakeholders. The article demonstrates the need for future research in the field of leader narcissism and opens up new avenues for inquiry.